Glomerular hyperfiltration with hyperglycemia in the spontaneously diabetic Torii (SDT) fatty rat, an obese type 2 diabetic model - Sano, R; Ishii, Y; Yamanaka, M; Yasui, Y; Kemmochi, Y; Kuroki, F; Sugimoto, M; Fukuda, S; Sasase, T; Miyajima, K; Nakae, D; Ohta, T (Physiological research, 2021)
Glomerular hyperfiltration is observed in an early stage of kidney diseases including diabetic nephropathy. A better understanding of pathophysiological changes in glomerular hyperfiltration is essential for development of new therapies to prevent kidney disease progression. In this study, we investigated glomerular changes including glomerular filtration rate (GFR) and glomerular size in the Spontaneously Diabetic Torii (SDT) fatty rat, an obese type 2 diabetic model, and we also evaluated pharmacological effects of the sodium glucose cotransporter 2 inhibitor dapagliflozin on the renal lesions. Dapagliflozin was administered to SDT fatty rats from 5 to 17 weeks of age. Blood and urinary biochemical parameters were periodically measured. GFR was determined by transdermal GFR monitor at 16 weeks of age and histopathological analysis was performed at 17 weeks of age. SDT fatty rat developed severe hyperglycemia and exhibited pathophysiological abnormalities in the kidney, such as an increased GFR, glomerular hypertrophy and tissue lesions. Dapagliflozin achieved good glycemic control during the experimental period, inhibited the increase in GFR, and improved histopathological abnormalities in tubules. These results suggest that the SDT fatty rat is a useful model for analyzing the pathogenesis of diabetic nephropathy during its early stage and dapagliflozin improves not only hyperglycemia but also glomerular hyperfiltration and tubule lesions in SDT fatty rat.
Keywords: obezita; glukosidy; Diabetes Mellitus, Experimental; Sodium-Glucose Transporter 2 Inhibitors; experimentální diabetes mellitus; Benzhydryl Compounds; Glomerular Filtration Rate; krysa rodu Rattus; zvířata; hodnoty glomerulární filtrace; hyperglykemie; Diabetes Mellitus, Type 2; Hyperglycemia; potkani Sprague-Dawley; diabetické nefropatie; Male; glifloziny; Diabetic Nephropathies; Rats; Glucosides; Obesity; Rats, Sprague-Dawley; Animals; benzhydrylové sloučeniny; mužské pohlaví; diabetes mellitus 2. typu; Disease Models, Animal; modely nemocí na zvířatech